CARACTERIZAÇÃO E QUANTIFICAÇÃO MINERALÓGICA DA FRAÇÃO ARGILA DO HORIZONTE Bi DE CAMBISSOLOS DA REGIÃO DE IRATI, PARANÁ, PELO MÉTODO DE RIETVELD - Martins, Elisandra Carolina (2010)
In order to better benefit from agriculture development it is necessary to know the soil physical and chemical properties which enable the reposition of nutrients through mineral and organic fertilization in the correct way. These soil properties might vary according to the content and composition of minerals in the clay fraction. In such a context the objective of this work was to characterize minerals from the clay fraction, of the Bi diagnostic horizon, of seven cambisols from the Irati region in the State of Paraná. For the characterization, clay fraction and air dried fine earth from Bi horizon of these soils were studied. Firstly, the particles density was determined using the pycnometer method in order to be used later for the sedimentation calculation through the Stokes Law and to obtain the clay fraction through physical fractioning, which also determined soil texture. Mineralogical analysis was carried out employing X-ray diffraction supported by the knowledge of local geology, with this data and the Rietveld method, the quantification of crystalline phases in the clay fraction was carried out. X-ray fluorescence technique was employed as elemental analysis, in order to compare to the results obtained by the Rietveld method. The average particle density obtained was 2,54 gcm-3. Textural class according to the American classification was very clayey for one of the samples and clayey for the others. The Rietveld method refinement presented good adjustment, with χ2 varying from 1,54 to 6,23. Elemental comparison between the fluorescence and the Rietveld method presented some divergences, which were granted to crystal imperfections, chemical composition variation and the presence of amorphous substances, which hampered the adjustment through the Rietveld Method and might lead to mistakes in the elemental quantification. From eight to nine mineral phases were identified in each sample of the clay fraction. The majority mineral phases for this fraction were kaolinite, muscovite and quartz, illite in some samples and in lower amounts hematite, goethite, gibbsite, lepidocrocite and calcite. These minerals are in accordance with the geology and are usually associated among themselves, mainly in young soils, in which weathering was not enough to transform the minerals entirely.